Organ‐on‐a‐Chip: Ex vivo Dynamics of Human Glioblastoma Cells in a Microvasculature‐on‐a‐Chip System Correlates with Tumor Heterogeneity and Subtypes (Adv. Sci. 8/2019). Issue 8 (17th April 2019) - Xiao, Yang; Kim, Dongjoo; Dura, Burak; Zhang, Kerou; Yan, Runchen; Li, Huamin; Han, Edward; Ip, Joshua; Zou, Pan; Liu, Jun; Chen, Ann Tai; Vortmeyer, Alexander O.; et al.
Abstract : In article1801531, Rong Fan and co‐workers examine the dynamics of brain tumor cells in a microvasculature‐on‐a‐chip system. Tumor cells residing in the perivascular zone show various degrees of co‐localization with microvessels across ten glioblastoma patients. Single‐cell transcriptome sequencing (21 750 single cells) reveals that brain tumor cells with high expression of PDGFRA preferentially localize in the perivascular niche.